Effect of casting solvent and polymer on permeability of propranolol hydrochloride through membrane-controlled transdermal drug delivery system - Murthy, Talasila Eswara Gopala Krishna; Saikishore, Vankayalapati (Asian Journal of Pharmaceutics (AJP), 2014)
In the present work, cellulose acetate (CA), ethyl cellulose (EC), and Eudragit RS 100 (ERS100) films were prepared and evaluated as rate-controlling membranes for transdermal drug delivery systems. Acetone-methanol (8:2), chloroform- methanol (8:2), dichloromethane-methanol (8:2), and ethyl acetate-methanol (8:2) were used as solvents in the preparation of films. Dibutyl phthalate or propylene glycol at a concentration of 40% w/w of the polymer was used as a plasticizer in the preparation of CA and EC films. Dibutyl phthalate at a concentration of 15% w/w of the polymer was used as a plasticizer in the preparation of ERS100 films. The solvent evaporation technique was employed for the preparation of CA and EC films, and the casting solvent technique was employed for the preparation of ERS100 films. The dry films were evaluated for physical appearance, thickness uniformity, folding endurance, water vapor transmission (WVT), drug diffusion, and permeability coefficient. Both WVT and drug diffusion rate followed zero-order kinetics. The mechanism of drug release was governed by Peppas model.The diffusion exponent of release profiles (slope) has a value of 1.0360-1.3147 (n > 1), which indicates super case II transport diffusion. The results obtained in the present study thus indicated that the polymers and solvents used for the preparation of films have shown significant influence on the WVT, drug diffusion, and permeability of the films.